Oesophageal function before, during, and after healing of erosive oesophagitis. Issue 2 (February 1988) - Baldi, F; Ferrarini, F; Longanesi, A; Angeloni, M; Ragazzini, M; Miglioli, M; Barbara, L
Abstract : In order to investigate the relationship between oesophageal motor abnormalities and oesophagitis, we carried out four hour studies of oesophageal motility and 24 hour pH measurements in fasting and fed conditions in eight patients before, during (pH only), and after medical healing of erosive oesophagitis. Gastrooesophageal acid reflux decreased (ns) during the treatment, but tended to return to basal values at the end. Oesophageal body motility was unchanged after healing, while the lower oesophageal sphincter basal tone was significantly increased at the end of the study in the postcibal period. The results suggest that the impairment of the sphincter tone in reflux oesophagitis is secondary to the presence of the oesophageal lesions. Macroscopic healing is not paralleled by improved major pathogenic factors of the disease, however--that is, acid reflux and oesophageal body motility.